Auxiliary inductances design of a bidirectional three-port DC-DC converter - Piris Botalla, Laureano Enrique (2016)
This paper proposes a methodology to design the auxiliary inductances of a bidirectional three-port DC-DC converter, which allows minimize the currents through the high frequency transformer and switches. In this way, RMS current and also the current values at the switching instants, as function of auxiliary inductances, are analyzed considering the different operating conditions. From this analysis, design considerations for these inductances are determined. Finally, experimental results are presented to validate the theory.